AI in drug discovery: A wake-up call. Issue 1 (January 2023) - Urbina, Fabio; Lentzos, Filippa; Invernizzi, Cédric; Ekins, Sean
Highlights: We described previously the misuse of generative AI used in drug discovery. We now share further unpublished details on the experiment. We place our experiences in the larger frame of other powerful technologies. We provide a wake-up call for users of generative AI.